PrEP and Our Youth: Implications in Law and Policy - Burda, Jason Potter (Columbia Journal of Gender and Law, 2015)
Truvada®, an antiretroviral medication originally approved to treat human immuno-deficiency virus (HIV), is the first drug to receive FDA approval for use by HIV-negative individuals to actually prevent infection. The prophylactic use of an antiretroviral such as Truvada is a pharmacological prevention method called “HIV pre-exposure prophylaxis” (or “PrEP’). With an efficacy of over ninety percent when used as prescribed, Truvada as PrEP has been embraced by the public health community, and implementation is under way across the United States. Truvada as PrEP is currently indicated for adult use only, but it may also be prescribed off-label to at-risk youth. In this Article, I draw upon public health, neurodevelopmental, and psychosocial research to argue that PrEP is a necessary tool in the fight against HIV among youth. Thus, exploring the challenges of delivering PrEP to at-risk youth is essential. As a general rule, states mandate the involvement of parental figures in the healthcare of minors. However, recognizing that parental involvement in sensitive matters such as sexually transmitted infection (STI) treatment is a barrier to reaching youth, legislators have crafted limited exceptions to this rule. With the goal of locating inroads to confidential PrEP access in these exceptions, I survey STI, emancipation, and emergency consent laws, develop frameworks for navigating them, and suggest that STI laws offer the most promise of offering confidential PrEP access. Further, I posit that providing PrEP at clinics receiving Title X family planning funds, which must offer confidential services to youth, may be a national means of achieving that end. Yet guaranteeing accessibility is only one piece of the delivery puzzle; guaranteeing acceptability is a second. As such, I propose the addition of PrEP to sexual education programming funded by grants from the ACA s Personal Responsibility Education Program, which would ensure that curricula include PrEP alongside more established prevention methods such as condoms. Overcoming these barriers will pave the way for rapid uptake of future HIV prevention innovations for and among the most vulnerable: our youth.